Factors Affecting the Competence of Employees at the ASN Land Office at the Ministry of ATR/BPN - Agustyarsyah, Agustyarsyah (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines the factors that affect the competence of employees at the Land Office ASN at the Ministry of ATR/BPN. The variables tested in this study are transformational leadership and work environment as exogenous variables and employee competence as endogenous variables. In contrast, work motivation as mediators and work stres variables as moderators. Which fits with empirical data on Land Office Employees at the Ministry of ATR/BPN. The study’s respondents were employees who had taken the conpetency assessment at the level of Administrator Position, Supervisory Position and Executive Position, which was 319 employees. Data analysis using Structural Equation Model (SEM) with the help of SmartPLS software. Based on the results of the hypothesis test, the average Loading factor value is > 0.70, the composite reliability value > 0.70, the t-statistic value > 1.96 or the p-value < 0.05 (5%) and can be interpreted as a significant influence between the independent variable and the dependent variable. The results showed that transformational leadership, work environment, and work motivation affect employee competence. Work motivation was able to mediated the influence of transformational leadership and work environment on employee competence, still work stress was found to weaken the influence of the work environment on employee competence.